Seafaring Practice and Narratives in Homer's Odyssey. (2019) - Mann, Rupert
Abstract: It is intrinsically plausible that the Odyssey, which freely uses realistic details of many aspects of life on and beside the sea, was informed by real seafaring experience. This paper corroborates that hypothesis. The first part catalogues parallels between details of Odyssean and real-world seafaring. Odyssean type-scenes in particular echo real practice. The second part argues that three larger episodes have real-world parallels—the visit to the Lotos Eaters anticipates incidents of sailors deserting in friendly ports; the escape from Skylla and Charybdis demonstrates a safe course through a turbulent strait, and the encounter with Ino / Leukothea foreshadows the contemporary phenomenon of a sensed presence during a crisis. The pattern of coincidence between the Odyssey and the real world of seafaring constitutes a cumulative argument that suggests that those episodes in particular, and the poem as a whole, was informed by that world—a conclusion with consequences both for our understanding of the poem, and for our knowledge of the early Mediterranean maritime.